(untitled) (European Journal of Pure and Applied Mathematics, 2025)
Solving the Split Equality Fixed-Point Problem (SEFPP) often requires computing the norms of bounded and linear operators, a task that can be computationally demanding. To tackle this challenge, we investigated the SEFPP for quasi-pseudocontractive mappings in Hilbert spaces and proposed innovative viscosity algorithms to solve the problem. We established the strong convergence of these algorithms under appropriate conditions. To validate our theoretical results, we conducted numerical experiments, which not only confirmed the efficacy of our results but also demonstrated their advantages over existing methods in the literature. Our work generalizes and extends several significant results from prior research, contributing to the broader understanding of fixed-point problems and related problems.